Determination of Copper in Quince Samples with a Matrix Matching Strategy Using Vortex Assisted Deep Eutectic Solvent-Based Emulsification Liquid Phase Microextraction - Slotted Quartz Tube - Flame Atomic Absorption Spectrometry - Borahan, Tulay; Unutkan, Tugce; Zaman, Buse Tugba; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2020)
A vortex assisted deep eutectic solvent-based emulsification liquid-phase microextraction method was developed for the extraction and preconcentration of copper at trace levels followed by determination with slotted quartz tube - flame atomic absorption spectrometry. Various experimental factors were systematically optimized by performing single variant experiments to enhance detection power. Under the optimized conditions, the calibration plot showed linearity in the concentration range from 2.5 to 100 mu g L-1. The developed method offered limits of detection and quantification equal to 0.5 and 1.8 mu g L-1, respectively. The relative standard deviation (n = 6) for the lowest concentration of the calibration plot was lower than 6.0% which demonstrates good precision. The enhancement in the detection power was 160-fold by the developed vortex assisted deep eutectic solvent-based emulsification liquid phase microextraction - slotted quartz tube - flame atomic absorption spectrometry method. The validity and accuracy of the proposed method were confirmed through recovery experiments on quince samples. Acceptable percent recoveries in the range from 93.6 to 117.6% were obtained.
Keywords: Copper; deep eutectic solvent; flame atomic absorption spectrometry; liquid-phase microextraction; CLOUD POINT EXTRACTION; COLORIMETRIC DETERMINATION; WATER SAMPLES; LEAD; MERCURY; GREEN; ZINC; PRECONCENTRATION; VEGETABLES; ADSORBENT; Chemistry